La Mamma Interrogating a National Stereotype (New York : Palgrave Macmillan US, 2018)
The idea of the "mamma italiana" is one of the most widespread and recognizable stereotypes in perceptions of Italian national character both within and beyond Italy. This figure makes frequent appearances in jokes and other forms of popular culture, but it has also been seen as shaping the lived experience of modern-day Italians of both sexes, as well as influencing perceptions of Italy in the wider world. This interdisciplinary collection examines the invented tradition of mammismo but also contextualizes it by discussing other, often contrasting, ways in which the role of mothers, and the mother-son relationship, have been understood and represented in culture and society over the last century and a half, both in Italy and in its diaspora.
1. La Mamma: Italian Mothers Past and Present: Penelope Morris and Perry Willson -- 2. Mammismo/Momism: On the History and Uses of a Stereotype, 1940s to the Present: Silvana Patriarca -- 3. Mothers, Workers, Citizens: Teresa Noce and the Parliamentary Politics of Motherhood: Molly Tambor -- 4. Problems and Prescriptions: Motherhood and Mammismo in 1950s Advice Columns: Penelope Morris -- 5. Conceptualizing the Maternal: Representations, Reflections and Refractions in Women's Literary Writings: Ursula Fanning -- 6. Neapolitan Mothers: Three Generations of Women, from Representation to Reality: Gabriella Gribaudi -- 7. Mammas in Italian Migrant Families: the Anglophone Countries: Maddalena Tirabassi -- 8. Queer Daughters and Their Mothers: Carole Maso, Mary Cappello, and Alison Bechdel Write Their Way Home: Mary Jo Bona -- 9. Beyond the Stereotype: the Obstacle Course of Motherhood in Italy: Chiara Saraceno.-.
Literature, Cultural and Media Studies
text file PDF
Keywords: European literature; Motion pictures-History.; Literature, Modern-20th century; Sociology; Literature-Philosophy.; Culture-Study and teaching